Fruiting phenology of palms and trees in an Atlantic rainforest land-bridge island - Genini, Julieta; Galetti, Mauro; Morellato, L. Patricia C. (Flora. Morphologie, Geobotanik, Oekophysiologie, 2009)
Tropical forests show periods of scarcity and high fruit production in the same year and/or between years. Palms are an important component of Neotropical rainforests and a significant food resource for several frugivores. Therefore, their role as keystone resource may be exacerbated in highly impoverished areas. In Anchieta Island, São Paulo/Brazil, human settlements have modified and impoverished the forest, mainly through overharvesting and the introduction of exotic plants and several mammal species. We assessed the offer of fruits consumed by vertebrate frugivores at this island, the vegetation of which is belonging to the Brazilian Atlantic rainforest. We compared whether the fruiting patterns and fruit fall differ between palms and trees, and discuss the importance of palms as a food resource for frugivores and the implications for Anchieta Island conservation. Phenological patterns were seasonal for both trees and palms; however, the times of fruiting occurrence differed. Fruit fall biomass was at least twice lower than reported for other Atlantic rain forests and was also different between trees and palms. Palms contributed more than 80% of the overall fruit fall biomass. Palms may constitute an alternative food resource in periods of low fruit availability, although they do not provide resources for the entire assemblage of vertebrate frugivores. Energy-rich fruits, such as those produced by palms, may play an important role in the maintenance of frugivore populations in isolated, disturbed environments with a high density of vertebrate frugivores, low diversity of fruiting species and fruit biomass such as those found on Anchieta Island.